Respuesta :

This is a composite that could also be written in the form f(g(x)).  Take the function defined as g(x) and stick it in in place of the x in f(x).  Like this: [tex]f(g(x))=(x-3) ^{2} -2[/tex].  And that's it.
For this case we have the following functions:
 [tex] f (x) = x ^ 2 - 2 g (x) = x - 3[/tex]
 We must make the following composition of functions:
 [tex] (fog) (x) [/tex]
 This composition of functions means that we must replace the function g (x) in the function f (x) in the following way:
 [tex] f (g (x)) [/tex]
 We have then:
 [tex] f (g (x)) = (x - 3) ^ 2 - 2 [/tex]
 Rewriting we have:
 [tex] f (g (x)) = x ^ 2 - 6x + 9 - 2 f (g (x)) = x ^ 2 - 6x + 7[/tex]
 Answer:
 [tex] f (g (x)) = x ^ 2 - 6x + 7 [/tex]
 option 2